NARRATING THE INDIAN NATION A NONINDIAN PERSPECTIVE: A STUDY OF WILLIAM DALRYMPLE'S THE LAST MUGHAL AND RUDYARD KIPLING'S KIM - Syamala Kallury; Suman Sigroha (Celt: A Journal of Culture, English Language Teaching & Literature, 2008)
This paper deals with tile issue of tile rise of nationalism in Indian context as a result of tile events of 1857. and attempts to study the perspectives of two non-Indian writers interested in Indian nation. namely Rudyard Kipling and William Dalrymple in their novels Kim and The Last Mughal respectively as opposed to tile Indian nationalist perspectives seen and portrayed in later narratives by Indians. The former is a fictional representation of the mutiny of 1857 whereas tile latter is a fictionalized historical account. Published almost a hundred years apart. and coming at different defining moments in India's history. the two novels Kim (/901) and The Last Mughal (2006). both talk of a common set of events. It is one endeavor to see the different dimensions explored by these two writers.